From Global Norms to Local Practices: the Internalization of Children's Rights in Makassar through UNICEF Assistance - Abdullah, Nurjannah; Hastira, Muhammad Fajhriyadi; Hastira, Muh Fichriyadi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
Abstract: This study aims to understand how UNICEF, as a foreign aid actor, plays a role in internalizing children's rights norms into local policies and practices in Makassar City. The issue examined stems from the gap between global commitments through the Convention on the Rights of the Child (CRC) and the reality of child protection at the local level. A qualitative approach with a case study strategy was used, as it is appropriate for exploring complex experiences, perspectives, and social processes. Data was collected through in-depth interviews with members of the Makassar Children's Forum (FAM) and officials from the Makassar City Women's Empowerment and Child Protection Agency (DP3A); supplemented by participatory observation and analysis of official documents such as mayoral regulations, UNICEF reports, and training modules. The thematic analysis results show that the internalization of children's rights norms occurs through three main channels: technical assistance, policy advocacy, and community capacity building. This process follows the Norm Life Cycle pattern while undergoing adaptation through norm localization mechanisms. FAM acts as a norm translator that connects global values with local culture, such as siri and gotong royong. This study contributes theoretically by expanding the discourse on foreign aid as an instrument for norm diffusion, and practically by emphasizing the importance of local ownership in the sustainability of child protection. The findings suggest the need for stronger cultural translation strategies in child protection policies and programs at the regional level.